Doubling the number of health graduates in Zambia: estimating feasibility and costs - Lee Joanne; Libetwa Miriam; Kapihya Margaret; Tjoa Aaron; Pattinson Charmaine; McCarthy Elizabeth; Schroder Kate (BMC, 2010)
Abstract Background The Ministry of Health (MoH) in Zambia is operating with fewer than half of the human resources for health (HRH) necessary to meet basic population health needs. Responding urgently to address this HRH crisis, the MoH plans to double the annual number of health training graduates in the next five years to increase the supply of health workers. The feasibility and costs of achieving this initiative, however, are unclear. Methods We determined the feasibility and costs of doubling training institution output through an individual school assessment framework. Assessment teams, comprised of four staff from the MoH and Clinton Health Access Initiative, visited all of Zambia's 39 public and private health training institutions from 17 April to 19 June 2008. Teams consulted with faculty and managers at each training institution to determine if student enrollment could double within five years; an operational planning exercise carried out with school staff determined the investments and additional operating costs necessary to achieve expansion. Cost assumptions were developed using historical cost data. Results The individual school assessments affirmed the MoH's ability to double the graduate output of Zambia's public health training institutions. Lack of infrastructure was determined as a key bottleneck in achieving this increase while meeting national training quality standards. A total investment of US$ 58.8 million is required to meet expansion infrastructure needs, with US$ 35.0 million (59.5%) allocated to expanding student accommodation and US$ 23.8 million (40.5%) allocated to expanding teaching, studying, office, and dining space. The national number of teaching staff must increase by 363 (111% increase) over the next five years. The additional recurring costs, which include salaries for additional teachers and operating expenses for new students, are estimated at US$ 58.0 million over the five-year scale-up period. Total cost of expansion is estimated at US$ 116.8 million over five years. Conclusions Historic underinvestment in training institutions has crippled Zambia's ability to meet expansion ambitions. There must be significant investments in infrastructure and faculty to meet quality standards while expanding training enrollment. Bottom-up planning can be used to translate national targets into costed implementation plans for expansion at each school.